Treatment of asymmetrical vernal keratoconjunctivitis with supratarsal corticosteroid injection - Thanathanee, Onsiri (BMJ Case Rep, 2014)
A 6-year-old Thai girl presented with itching, redness and copious discharge in both eyes. Slit-lamp biomicroscopy of the left eye revealed cobblestone papillae with marked ptosis while in the right eye only small papillae were observed. Punctuate epithelial keratitis was noted only in the left eye. There were no associated factors for giant papillary conjunctivitis (ie, suture or contact lens). The cobblestone papillae in the left eye persisted after maximal topical and oral antiallergic medications. Two doses of supratarsal corticosteroid (20 mg of triamcinolone acetonide) injection without any topical or oral antiallergic medications were undertaken in the left eye 1 month apart. Cobblestone papillae and punctate epithelial erosion (including allergic symptoms) were completely recovered. There was no recurrence after 18 months of follow-up. This case report indicates that using supratarsal corticosteroid injection by itself in recalcitrant vernal keratoconjunctivitis provides promising results.